Interferon Gamma-Based Detection of Latent Tuberculosis Infection in the Border States of Nuevo Leon and Tamaulipas, Mexico - Oren, Eyal; Alatorre-Izaguirre, Gabriela; Vargas-Villarreal, Javier; Moreno-Treviño, Maria Guadalupe; Garcialuna-Martinez, Javier; Gonzalez-Salazar, Francisco (Frontiers in Public Health, 2015)
Nearly one-third of the world’s population is infected with latent tuberculosis (LTBI). Tuberculosis (TB) rates in the border states are higher than national rates in both countries, with the border accounting for 30% of total registered TB cases in both the US and Mexico. However, LTBI rates in the general population in Mexican border states are unknown. In this region, LTBI is diagnosed using the tuberculin skin test (TST). New methods of detection more specific than TST have been developed, although there is currently no gold standard for LTBI detection. Our objective is to demonstrate utility of the Quantiferon TB gold In-Tube (QFT-GIT) test compared with the TST to detect LTBI among border populations. This is an observational, cross-sectional study carried out in border areas of the states of Nuevo Leon and Tamaulipas, Mexico. Participants (n=210) provided a TST and blood sample for the QFT-GIT. Kappa coefficients assessed agreement between TST and QFT-GIT. Participant characteristics were compared using Fisher Exact tests. Thirty-eight percent of participants were diagnosed with LTBI by QFT-GIT. The proportion of LTBI detected using QFT-GIT was almost double (38% [79/210]) that found by TST (19% [39/210]) (P<0.001). Concordance between TST and QFT-GIT was low (Kappa = 0.37). We recommend further studies utilizing the QFT-GIT test to detect LTBI among border populations.